SPILITIZED PILLOW-HYALOCLASTITE SEQUENCE FROM ANDAMAN OPHIOLITE, INDIA: EMPLACEMENT AND ALTERATION IN A SUBMARINE ENVIRONMENT - Duraiswami, Raymond; J. Monteiro, Aristle; N. Shaikh, Tahira; Akhter, Qazi (Ofioliti, 2022)
The Corbyn’s Cove area in south Andaman Island exposes a ~ 30 m thick sequence of sheet lavas, pillows and hyaloclastite deposits related to the Andaman Ophiolite, India. The upper sheet lavas are emplaced as tabular forms with thick, jointed core, vesicular crust and patchy hyaloclastite. The sheet lavas are criss-crossed by a network of calcite veins. The pillows constitute a modest flow field at the base of the sheet lavas and contain small (4.55 x 5.18 cm) to large (60.89 x 113.86 cm), spherical, non-vesicular, glassy entities. Pillow interiors contain radial and concentric joints. Absence of vesicles suggests that the pillows have been emplaced subaquaeously at depths greater than 4 km. The pillow lavas are fed by dykes. Thick hyaloclastite deposits containing sporadic patches of pillow breccias are intricately associated with the pillows in mound-like progradational bird foot deltas. In thin sections, the pillow lavas are characterized by lanceolate plagioclase and fretted pyroxene quenched morphologies in a holohyaline texture indicating high degrees of undercooling (ΔT ~ 100 to 200°C). Plagioclase compositions range from Anorthite (An97-99) in the core to Albite (An1-9) in the glassy margin. Individual plagioclase phenocryst in the dyke and pillow interior show tabular forms (ΔT ~ 50°C), with effects of albitization of the margin (An1-10; S-D index - 1.89 to 65.57) and variable alteration in the core (PI - 20.84 to 37.14; CIA - 70.92 to 99.34). Geochemically, the dyke-pillow lavas are hypersthene-normative tholeiites that have undergone variable degrees of spilitization and alteration. The sheet lavas have higher concentrations of Cs, Rb, Ce, U, K, Sr, P, Zr and Yb relative to N-MORB due to post emplacement cryptic metasomatism related to the calcite stockwork. These episodes of alteration have influenced the mineralogy and geochemistry of the original lavas. The geochemistry of the lavas indicates that they were deposited in a MORB-like environment, with a possible back-arc affinity. We envisage that the entire sequence from Corbyn’s Cove was emplaced subaqueously during the Late Cretaceous in the Indo-Sino Burmese sea along the flanks of a rising mid oceanic ridge where the magma (1222 to 1230°C; 6 to 8 kbar) was generated at shallow depths (~ 20 km) and erupted to the surface as dykes that fed the pillow lava flow fields. Spilitization of the pillow lavas to various degrees occurred at temperatures between 1218 to 1164ºC and even lower while the hydothermal alteration took place at temperatures well below 300°C.